Bayesian maximum entropy interpolation analysis for rapid assessment of seismic intensity using station and ground motion prediction equations - Kang, Dengjie; Chen, Wenkai; Jia, Yijiao (Frontiers in Earth Science, 2024)
The Bayesian maximum entropy (BME) spatial interpolation analysis method is used to explore the effective combination of seismic station data and the ground motion prediction equation (GMPE) is applied to establish a seismic intensity assessment map based on the obtained results. The results indicate that: (1) According to the intensity analysis results. Soft data in the Japanese earthquake analysis caused overestimation of affected areas, but BME corrected this, especially at the epicenter. Similarly, U.S. earthquakes improved rupture direction predictions. (2) Compared with other spatial interpolation methods, the profile results show that the BME results of the Japanese earthquake and the Turkey earthquake are more consistent with the ShakeMap results than IDW and Kriging, and IDW has low intensity anomaly areas. (3) The BME method overcomes the significant deviation between the intensity assessment results and the actual damage situation when moment magnitudes are small, accurately delineates the scope of the earthquake-stricken areas and enriches the postearthquake processing of information and data in disaster areas. The proposed method is broadly applicable, and when there are only soft data or few stations with data, the BME method can still be effectively used for interpolation analysis.